Performance analysis based on GPS data of Olympic class windsurfing - Chun, S.; Park, J.; Kim, T.; Kim, Y. (International Journal of Performance Analysis in Sport, 2022)
This study examined the technical and tactical variables that determine performance before departure and during a race in all wind conditions. Data were collected from 44 Olympic-class windsurfers who participated in the World Cup and Allianz Regatta. Distance to the start line and speed 5 s before departure, distance to start line and speed when starting, and distance travelled and time at each leg were recorded via GPS (5 Hz). Average speed was calculated through distance travelled and time. Results indicated that the high-performance group had significantly (p < 0.05) less distance from the starting line and faster speed when starting than the low-performance group in heavy wind conditions. During the first or third legs with light and medium winds, the high-performance group demonstrated a significantly (p < 0.05) faster average speed in heavy wind and significantly less distance travelled, and faster average speed was observed in all legs. The first half of the high-performance group had significantly (p < 0.05) longer distance travelled than the second half. Significantly faster average speed was observed in light wind. These results may assist in preparing for the tactical and technical requirements during a race and enhance performance in every situation.